Comparison of customer service between Janata Bank Ltd and BRAC Bank Ltd - Haque, Tasfin Iftekharul (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.